(untitled) (Journal of Medical & Health Sciences Review, 2025)
Cancer-associated fibroblasts (CAFs) are pivotal components of the tumor microenvironment (TME) that critically influence the progression and therapeutic resistance of oral squamous cell carcinoma (OSCC). This review provides an in-depth synthesis of current knowledge regarding the diverse roles of CAFs in OSCC, emphasizing their contributions to tumor growth, angiogenesis, metastasis, immune modulation, and drug resistance. CAFs, which originate from normal fibroblasts through activation processes such as TGF-β signaling and epithelial-mesenchymal transition, exhibit distinct markers including α-smooth muscle actin (α-SMA), fibroblast activating protein (FAP), and fibroblast specific protein-1 (FSP-1). Unlike their normal counterparts, CAFs secrete a complex array of cytokines and growth factors, such as IL-6, IL-8, vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), and hepatocyte growth factor (HGF), which activate oncogenic pathways including EGFR, Wnt/β-catenin, Hippo, and JAK2-STAT3. These signaling networks facilitate not only enhanced tumor cell proliferation and invasion, but also the induction of epithelial-mesenchymal transition, thereby promoting metastasis. In addition, CAF-derived factors stimulate angiogenesis by recruiting endothelial progenitor cells and remodeling the extracellular matrix to support neovascularization. CAFs further contribute to an immunosuppressive TME by inducing T cell apoptosis and promoting M2 macrophage polarization, which impairs antitumor immunity. Notably, CAFs are implicated in resistance to conventional chemotherapies, underscoring their role in treatment failure. Targeting CAFs or their downstream effectors represents a promising therapeutic strategy to overcome drug resistance and improve patient outcomes. Overall, this review highlights the multifaceted impact of CAFs in OSCC and advocates for the development of CAF-directed therapies as an integral component of comprehensive cancer management. Future studies should aim to elucidate the molecular heterogeneity of CAFs and to develop innovative strategies that effectively target their tumor-promoting functions without compromising normal tissue integrity.